Long : Horizon Exchange Rate Predictability? - Giorgianni, Lorenzo; Berkowitz, Jeremy (Washington, D.C. : International Monetary Fund, 1997)
Several authors have recently investigated the predictability of exchange rates by fitting a sequence of long-horizon error-correction regressions. By considering the implied vector error-correction model, we show that little is to be gained from estimating such regressions for horizons greater than one time period. We also show that in small to medium samples the long-horizon procedure gives rise to spurious evidence of predictive power. A simulation study demonstrates that even when using this technique on two independent series, estimates, diagnostic statistics and graphical evidence incorrectly suggest a high degree of predictability of the dependent variable.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Diebold-Mariano Statistic; Error-Correction Term; Exchange Rate; Slope Coefficient; WP; United States